PENGHAMBATAN PERTUMBUHAN Aspergillus flavus DAN Fusarium moniliforme OLEH EKSTRAK SERUNI (Wedelia biflora) DAN KEMBANG BULAN (Tithonia diversifolia) - Agnes Dame Sinta Uli; Kiki Nurtjahja; Cut Fatimah Zuhra (Saintia Biologi, 2012)
The growth inhibition of Aspergillus flavus and Fusarium moniliforme by extract of seruni (Wedelia biflora) and Kembang bulan (Tithonia diversifolia) has studied. Kirby-Bauer disc diffusion were used in this experiment. The leaf methanolic extracts prepared were 0, 5, 10, 15, 30, 40, 50, 60 and 70% with dimethyl sulfoxide as the solvent. The results showed that extract of seruni and kembang bulan has a different activity in inhibiting the growth of both fungus. Seruni extract showed lower activity in inhibiting A. flavus and F. moniliforme than kembang bulan. In 40% seruni inhibits the growth both of the fungus. While kembang bulan showed activity in inhibiting A. flavus and F. moniliforme in 5%. Kata kunci: A. flavus, F. moniliforme, T. diversifolia and W. biflora exctract